2015
DOI: 10.1002/hed.24005
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck free flap surgical site infections in the era of the Surgical Care Improvement Project

Abstract: A surgical site infection rate of 13.3% was noted. In this cohort, with a compliance rate with prophylactic antibiotic measures, prior radiation was found to be a risk factor only in patients with cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E392-E398, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 32 publications
6
41
0
Order By: Relevance
“…All but one study in our meta‐analysis used this definition for surgical site infection . Furthermore, we must assume that antibiotics were given on time and dosed appropriately to achieve therapeutic steady‐state concentrations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All but one study in our meta‐analysis used this definition for surgical site infection . Furthermore, we must assume that antibiotics were given on time and dosed appropriately to achieve therapeutic steady‐state concentrations …”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Cystic Fibrosis and Genetic Disorders November 2004 study selection, quality assessment, and data extraction form were used to assess study quality and extract the pertinent data from each article that met inclusion criteria. Ultimately, 5 studies were appropriate for inclusion . From the identified studies, we extracted relevant clinical information regarding the number of patients receiving short‐term (≤24 hours) prophylactic antibiotics, the number of patients receiving long‐term (>24 hours) prophylactic antibiotics, and the risk of recipient surgical site infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All respondents in this study reported use of prophylactic antibiotics with surgeries communicating with the autodigestive tract, as is standard of care. Complex H&N cancer resections are typically clean‐contaminated cases, for which surgical wound infection rates of 8.1% to 41% have been reported . Furthermore, surgical site infection is a significant risk factor for readmission and free lap failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surgical site infection is a significant risk factor for readmission and free lap failure. Recent studies have shown evidence to support recommendations including use of prophylactic antibiotics for at least the first 24 hours of hospitalization, cautious use of clindamycin, and no benefit to duration greater than 1 week for free flap patients . There is currently no consensus on antibiotic regimen or duration otherwise.…”
Section: Discussionmentioning
confidence: 99%